The process of school sports initiation in volleyball: a look of renovation for its learning - Jorge Félix Arronte Mesa; Belkis Ferro González (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2020)
The process of school sports initiation in volleyball is a current issue in the field of scientific-educational research, which analyzed in relation to the context and the time in which it takes place, needs to enrich its contents from new pedagogical perspectives. The objective of this work is to characterize the process of school sports initiation of volleyball in the "Ormani Arenado LLonch" EIDE in Pinar del Río. To achieve this goal, methods of the theoretical level (historical-logical, inductive-deductive, modeling, analytical-synthetic) and of the empirical level (documentary review, observation, surveys, interviews) were used to delimit the essences of the object and to scientifically organize the obtaining of the research results. Among the results, there is the systematization carried out that allowed to determine tendencies in the development of the object, to define it and to establish three dimensions for its study (cognitive-procedural, management of the methodological work and axiological) with its respective definitions, to specify strengths and weaknesses that characterize it in the sport institution of reference, as well as the integration of results of the diagnosis in the establishment of its regularities. It is stated that the dimensions of the analyzed variable, in its current state, present affected aspects, understood as challenges that deserve to be treated by the High Performance Methodological Department.